Robust and distortion control dual watermarking in LWT domain using DCT and error correction code for color medical image - Singh, A. K. (Multimedia tools and applications, 2019)
This paper presents lifting wavelet transform (LWT) and discrete cosine transform (DCT) based robust watermarking approach for tele-health applications. For identity authentication, ‘signature watermark’ of size ‘64 × 64’ and ‘patient report’ of size ‘80’ characters are hiding into the host medical image. Further, the signature watermark is encrypted by message-digest (MD5) and ‘patient report’ is encoded by BCH error correcting code before embedding into the host image. Experimental demonstrations indicate that the method provides sufficient robustness and security against various attacks without significant distortion between cover and watermarked image. Further, our results proved that the method offer NC value more than 0.9214 for most of the considered attacks. Furthermore, it is evident from results our method shows the improvement in robustness to previously reported techniques under consideration while providing low computational complexity.